2010
DOI: 10.1016/j.ijcard.2008.12.213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on circulating hsCRP concentrations: A sub-study of the Achieve Cholesterol Targets Fast with Atorvastatin Stratified Titration (ACTFAST) study

Abstract: Background: Elevated C-reactive protein (CRP) concentration is a risk factor for cardiovascular events that may add prognostic information. Statin treatment is associated with significant reductions in CRP concentrations, which appear to be unrelated to the magnitude of LDL-cholesterol reduction. We investigated the effect of atorvastatin, across its dose range, on high sensitivity (hs)CRP in subjects at high cardiovascular risk. Methods: ACTFAST was a 12 week, prospective, multicenter, open-label trial in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 51 publications
2
19
1
Order By: Relevance
“…Indeed, one previous study showed that 3-week treatment with a-glucosidase inhibitors reduced the levels of inflammatory and cell adhesion markers in patients with T2DM (28). Furthermore, short-term statin treatment is reported to improve inflammation (29). In addition, our results showed a significant reduction of BMI in the conventional treatment group.…”
Section: Discussionsupporting
confidence: 59%
“…Indeed, one previous study showed that 3-week treatment with a-glucosidase inhibitors reduced the levels of inflammatory and cell adhesion markers in patients with T2DM (28). Furthermore, short-term statin treatment is reported to improve inflammation (29). In addition, our results showed a significant reduction of BMI in the conventional treatment group.…”
Section: Discussionsupporting
confidence: 59%
“…These results were recently verified in the Achieve Cholesterol Targets Fast with Atorvastatin Stratified Titration (ACTFAST) 1 and 2 studies [40][41][42]. ACTFAST was a 12 week, prospective, multicenter, open-label trial in which high-risk subjects were assigned to a starting dose of atorvastatin (10, 20, 40 or 80 mg/d) based on LDL-C and status of statin use at screening (772 previous statin use vs 1,345 statin-free patients), with a single up-titration at 6 weeks if needed.…”
Section: Statinsmentioning
confidence: 68%
“…Overall, LDL-C decreased by a mean of 42% in the statin-free group and by an additional 31% (over the statin used at baseline) in the statin-treated group [40,41]. Finally, the ACTFAST studies verified the statin-induced reduction in CRP levels in patients with the MetS [42]. The ACTFAST studies confirmed that a flexible starting dose of atorvastatin allows most patients with type 2 diabetes or the MetS to achieve their LDL-C target safely with the initial dose or just a single titration.…”
Section: Statinsmentioning
confidence: 82%
“…These results are similar to previous reports evaluating the effects of ezetimibe/simvastatin and atorvastatin on hs-CRP reductions in subjects with metabolic syndrome. 13,15,34 Conclusions This post hoc analysis is the first report evaluating the simultaneous achievement of specified LDL-C, non-HDL-C and Apo B levels in individuals with metabolic syndrome with and without AVD. The more efficacious therapies (ezetimibe/simvastatin 10/20-40 and atorvastatin 40 mg) were required for .80% of subjects with MetS with or without AVD to achieve the dual targets of LDL-C ,100 mg/dL and non-HDL-C ,130 mg/dL.…”
Section: Discussionmentioning
confidence: 85%